Structural and functional similarities in bunyaviruses: Perspectives for pan‐bunya antivirals. (11th February 2019) - ter Horst, Sebastiaan; Conceição‐Neto, Nádia; Neyts, Johan; Rocha‐Pereira, Joana
Summary: The order of Bunyavirales includes numerous (re)emerging viruses that collectively have a major impact on human and animal health worldwide. There are no vaccines for human use or antiviral drugs available to prevent or treat infections with any of these viruses. The development of efficacious and safe drugs and vaccines is a pressing matter. Ideally, such antivirals possess pan‐bunyavirus antiviral activity, allowing the containment of every bunya‐related threat. The fact that many bunyaviruses need to be handled in laboratories with biosafety level 3 or 4, the great variety of species and the frequent emergence of novel species complicate such efforts. We here examined the potential druggable targets of bunyaviruses, together with the level of conservation of their biological functions, structure, and genetic similarity by means of heatmap analysis. In the light of this, we revised the available models and tools currently available, pointing out directions for antiviral drug discovery.